Moments of Competitive Balance in Major League Soccer. (April 2022) - Sung, Hojun; Mills, Brian M.; Lee, Younghoon
In this paper, we investigate competitive balance in Major League Soccer and compare balance across talent acquisition policy regimes with a bias-corrected measure from 1996 to 2019. We evaluate multiple moments of the league talent distribution, and we add to past work by using multiple levels of aggregation that reveal heterogeneous results with respect to the distribution of talent within and across seasons. We show that there has been little improvement in competitive balance over the league's history, though there has been an increase in year-to-year stability in balance and a lower propensity for teams at the extremes of performance.